Equity Crowdfunding as a Performance Improvement Strategy for Micro, Small and Medium Enterprises (MSMEs) - Mohammad Ihsan; Perdana Siregar, Ade (Dinasti Publisher, 2023)
The growth of MSMEs is the result of the community's independent efforts and has a role to reduce poverty in the form of creating jobs for the community. The development of digital technology is currently growing rapidly, opening up opportunities for Micro, Small and Medium Enterprises (MSMEs) to be able to improve their business performance, including in overcoming capital problems. The application of the use of equity crowdfunding is influenced by internal factors of an organization, namely the financial resources of the organization. The objectives of this study are (1) to examine the influence of financial resources on the performance of MSMEs; (2) Assessing the effect of financial resources on equity crowdfunding; (3) To examine the effect of equity crowdfunding on the performance of MSMEs; (4) To examine the role of equity crowdfunding which is able to mediate the influence of financial resources on the performance of MSMEs. The data analysis method used is Structural Equation Modeling (SEM) measurements using SmartPLS software. The results of the study show that (1) equity crowdfunding shows a significant positive effect on MSME business performance, it is proven that the higher the equity crowdfunding from business actors, the MSME business performance will increase; (2) Financial resources show a significant positive effect on MSME business performance, it is proven that the better the financial resources owned by business actors, the MSME business performance will increase; (3) financial resources show a significant positive effect on equity crowdfunding, the better the financial resources owned by business actors, the better equity crowdfunding; (4) equity crowdfunding as a mediation of the influence of financial resources shows a significant positive effect on MSME business performance, where equity crowdfunding is considered a variable that strengthens financial resources in improving MSME business performance.